Contrastive topics decomposed - Michael Wagner (Semantics and Pragmatics, 2012)
The analysis of contrastive topics introduced in Büring 1997b and further developed in Büring 2003 relies on distinguishing two types of constituents that introduce alternatives: the sentence focus, which is marked by a FOC feature, and the contrastive topic, which is marked by a CT feature. A non-compositional rule of interpretation that refers to these features is used to derive a topic semantic value, a nested set of sets of propositions. This paper presents evidence for a correlation between the restrictive syntax of nested focus operators and the syntax of contrastive topics, a correlation which is unexpected under this analysis. A compositional analysis is proposed that only makes use of the flatter focus semantic values introduced by focus operators. The analysis aims at integrating insights from the original analysis while at the same time capturing the observed syntactic restrictions.